An Analysis upon Protection and Prevention of Child Maltreatment/Neglect in India: Safeguarding Child Rights and Building Non-violent Communities (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In India, child rights, protection from abuse and exploitation (street children, child labour, trafficking etc.) are intimately linked to poor socioeconomic conditions in a large population base. Whose responsibility is it to ensure the safe, protective and caring environment that every child deserves? The UN CRC does not absolve either family or community or society at large. But it firmly puts the onus on the State.Child maltreatment is a global problem but is more difficult to assess and manage in developing countries such as India where one-fifth of the world’s total child population resides. Certain forms of maltreatment such as feticide, infanticide, abandonment, child labour, street-begging, corporal punishment and battered babies are particularly prevalent in India. Most physicians still need to be sensitized in order to suspect child abuse on the basis of unexplained trauma, multiple fractures, parental conflict and other corroborative evidence.A culture of non-violence towards children needs to be built into communities in order to provide an environment conducive to the overall development of the child. Rehabilitation of abused children and their families requires a multi-disciplinary service including pediatricians, child psychologists and social workers, and the training of police forces in how to tackle the problem.